IMPROVING LEARNING OUTCOMES USING GOOGLE CLASSROOM-ASSISTED FLIPPED LEARNING - Asih Susiati (Universitas Negeri Padang, 2022)
This study aims to determine efforts to improve learning outcomes of biology students through flipped learning model assisted by Google Classroom on metabolic material at SMA Negeri 1 Cikarang Barat. The research subjects were all students of class XII IPA 4 at this school, total 36 students. Samples were taken by simple random. The average score of students before being treated was 64.86, and then learning outcomes increased to 74.86 in the first cycle, 80 in the second cycle, and 87.50 in the third cycle. The number of students who scored 78 increased in every cycle, namely: 50% in cycle I; 61.11% in cycle II; and 86.11 in cycle III. We conclude that our model can improve learning outcome of our students.